Banking on the future : the fall and rise of central banking - Davies, H.; Green, David (Princeton : Princeton University Press, 2010)
The book shows how monetary policy and financial stability concerns have drifted apart in recent years and the crucial role this dichotomy has played in the run up to the crisis. It seeks to set recent events in the context of the wider perspective-asking what central banks are for, why their role is critical to the functioning of market economies, how they can best go about fulfilling that role, and whether recent experience and historic perspective point to the need for further reappraisal and reform.
Includes bibliographical references (p. 301-316) and index.
rua 29/10/13
Loans
Keywords: Banks and banking, Central; Monetary policy